IoT flood monitoring system - Vajathan, Vimalan Pillai; Dhinagaran, Sachinn; Thivianathan, Timothy Nathan; Tamilamuthan, Shaarveen; Govindasamy, Sanjay (Universiti Teknologi MARA, Kedah, 2023)
The flood monitoring system is designed to provide real-time data and early warning capabilities for effective flood management. By utilizing a network of sensors deployed in flood-prone areas, the system continuously monitors key parameters such as water levels and rainfall intensity. The collected data is transmitted to a central monitoring platform, where advanced analytics algorithms analyze the data streams and generate alerts and warnings based on predetermined thresholds. This enables authorities to take proactive measures, issue timely evacuation notices, and allocate resources effectively. The system also incorporates visualization tools to present the data in a user-friendly manner, aiding in decision-making and post-flood analysis. Overall, the flood monitoring system enhances flood preparedness, response capabilities, and public safety, contributing to improved flood management and reduced damages.